Flume Experiments on the Oscillating Wall Jet Induced by the Swing Oblique Impingement Jet. (August 2019) - Zhao, Peng; Zhang, Minxi; Yu, Guoliang
Abstract: The flow characteristics of oscillating wall jets induced by swinging an oblique impingement jet in a rectangular flume is experimentally investigated. By using ultrasonic Doppler velocity profiler (UDVP), the phase-dependent velocity profiles, the phase-varying turbulence fluctuations, and the decay of the velocity along the downstream surface of the oscillating wall jets are observed in a two-dimensional plane. Results show that the mean velocity profile of the oscillating wall jet in the near-bed region generally follows the Weibull distribution, similar to the steady wall jet. Greater fluctuation magnitudes are produced by the oscillating wall jet at the low-speed provocation and high-speed suppression phases than that at the accelerating and decelerating phases. The velocity fluctuations increase with the increasing oscillating frequency. Both the oscillation offset and amplitude of the oscillating wall jet decay continuously with the spreading distance. The decay rate of oscillation offset along the downstream wall of the oscillating wall jet is higher than the velocity decay rate of steady wall jet, and slightly increases with the increment of the oscillating frequency. The oscillating amplitude decays exponentially with the downstream distance.